2012
DOI: 10.1002/14651858.cd007945.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Centralisation of services for gynaecological cancer

Abstract: Background Gynaecological cancers are the second most common cancers among women. It has been suggested that centralised care improves outcomes but consensus is lacking. Objectives To assess the effectiveness of centralisation of care for patients with gynaecological cancer. Search methods We searched the Cochrane Gynaecological Cancer Group Trials Register, CENTRAL (The Cochrane Library, Issue 4, 2010), MEDLINE, and EMBASE up to November 2010. We also searched registers of clinical trials, abstracts of sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 85 publications
(296 reference statements)
2
38
0
2
Order By: Relevance
“…5 An elevated CA125 was not determinant factors of OS in our study (p> 0.05) in our study. Similar to the study of Whoo et al 24 CA125 level was not influence on OS for OC. However we found that presence of recurrence had significant effect on survival in OC (p> 0.05).…”
Section: International Journal Of Hematology and Oncologysupporting
confidence: 86%
See 3 more Smart Citations
“…5 An elevated CA125 was not determinant factors of OS in our study (p> 0.05) in our study. Similar to the study of Whoo et al 24 CA125 level was not influence on OS for OC. However we found that presence of recurrence had significant effect on survival in OC (p> 0.05).…”
Section: International Journal Of Hematology and Oncologysupporting
confidence: 86%
“…Most patients diagnosed with OC, survival is theorized to be 100%, who are still alive after 5-years, are presumably living with the disease rather than living disease-free. 5 Our analysis demonstrated that the DFS was 18.3 months (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). The Surveillance, Epidemiology and End Results-SEER database from 1995 to 2007 with epithelial OC who were actively followed-up and age 20 years or older were included for analyzing OS in the United States (40.692 patients) and OS was 65%, 44%, and 36% at 2, 5, and 10 years, respectively.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Lord Darzi's 2007 report 1 recommended the reorganisation of London stroke and major trauma services into specialised centralised higher volume units catering for large populations with high-tech facilities and senior medical continuity. A number of studies [2][3][4][5][6][7][8][9] suggest that reconfiguring healthcare services into fewer consolidated units will lead to increase in high-quality care and better patient outcomes. Cost savings arguably resulting from the economies of scale is also one of the driving forces behind centralisation of healthcare services.…”
Section: Introductionmentioning
confidence: 99%